What the heavens declare : science in the light of creation - Jaeger, Lydia (Eugene : Cascade Books, 2012)
"In her latest book, What the Heavens Declare, Lydia Jaeger provides a detailed analysis of the role of the theistic doctrine of creation in the rise of modern science, with a particular focus on the natural order. As the author explains, despite the common use of the expression "laws of nature" by both scientists and laymen, there is a long-standing tradition of philosophical debate about, and even refusal of, the notion that laws of nature might exist independently of a divine or human mind. This work attempts to account for natural order in harmony with the religious worldview that significantly contributed to the original context in which modern science began: the world seen as the creation of the triune God."--Publisher's website.
The idea of creation -- From substantial forms to laws of nature -- The order of the created world -- The relational nature of knowledge -- Explaining the natural order.
Includes bibliographical references (pages 173-188) and indexes.
Description based on print version record.
Keywords: Religion and science; Creation -- Biblical teaching; Philosophical theology; Law (Philosophical concept); Creation -- Biblical teaching; Law (Philosophical concept); Philosophical theology; Religion and science; RELIGION / Christian Life / General; Electronic books